2022
DOI: 10.1029/2021ms002721
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating Microtopography in a Land Surface Model and Quantifying the Effect on the Carbon Cycle

Abstract: Northern peatlands are an important component of the global carbon (C) cycle due to their ability to slowly accumulate C into substantial storage reservoirs. The ability of northern peatlands to store C is due to a set of unique environmental conditions that include shallow water tables, moist acidic soils, low nutrient content, and cool temperatures (Loisel et al., 2021). These conditions, especially moist soils, slow microbial decomposition and reduce the rate at which C is released to the atmosphere through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…It is important to take into account these aspects together with terrain attributes and spatial resolutions for efficacious microtopographic data acquisition. Multiple studies have shown that remote sensing techniques, especially through ALS, TLS, and sUAS can produce high-resolution DEMs and provide fine-scale measurements of microtopography in natural ecosystems [25,26,32,33]. Some studies have used a combination of one or more remote sensing techniques to delineate natural and human features in the environment [72] but multi-platform remote sensing approaches are not yet commonly employed in combination to delineate microtopography, particularly in low relief forested environments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to take into account these aspects together with terrain attributes and spatial resolutions for efficacious microtopographic data acquisition. Multiple studies have shown that remote sensing techniques, especially through ALS, TLS, and sUAS can produce high-resolution DEMs and provide fine-scale measurements of microtopography in natural ecosystems [25,26,32,33]. Some studies have used a combination of one or more remote sensing techniques to delineate natural and human features in the environment [72] but multi-platform remote sensing approaches are not yet commonly employed in combination to delineate microtopography, particularly in low relief forested environments.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported the use of close-range remote sensing technologies to map fine-scale microtopography by using dense and highly accurate elevation data over reasonably large areas [25,[32][33][34][35]. However, this is a recent development, and researchers examining fine-scale processes or distributions have traditionally relied on labor-intensive manual field surveys.…”
Section: Microtopography With Close-range Remote Sensingmentioning
confidence: 99%
“…These relationships are reflected in our data establishing correlations between both canopy and relative-elevation with snow depth (figures 4(D) and (E)). Black spruce can reduce soil moisture through transpiration and direct interception of precipitation (Perron et al 2023), and higher relative-elevation locations have reduced soil moisture due to exiting runoff (Engstrom et al 2005, Graham et al 2022. In this way, dense canopy and high relative-elevation keep hummock locations drier (table 1), and therefore, cooler during the warm-season (figures 5(D) and (F)).…”
Section: Hummock and Hollow Location Thaw Was Controlled By Canopy Co...mentioning
confidence: 99%
“…Previous research has established that permafrost thaw causes a net loss of soil organic carbon in peatlands due to inadequate surface accumulation rates to compensate for deep organic carbon losses during thawing, which also highlights the importance of spatial heterogeneity in the carbon budget estimation of high-latitude permafrost peatlands [17]. The microtopography of peatland affects soil organic carbon components, soil fauna, enzyme activity, microbial biomass, and microbially regulated greenhouse gas emission processes [18][19][20]. Moreover, microtopography can mediate soil hydrothermal processes and nutrient movements that may further affect microbial community composition and diversity in the soil [21].…”
Section: Introductionmentioning
confidence: 99%